An arginine-functionalized stationary phase for hydrophilic interaction liquid chromatography1. Issue 12 (21st June 2015) - Wu, Shengjie; Li, Xiuling; Zhang, Feifang; Jiang, Ge; Liang, Xinmiao; Yang, Bingcheng
<x xml:space="preserve">Abstract</x> A arginine-functionalized HILIC stationary phase has been prepared for the first time by clicking arginine onto silica gel. As an HPLC column, it offered the efficient separation of highly polar analytes. As a SPE sorbent, it exhibited excellent selectivity and enrichment toward acidic glycopeptides.